Challenging gender and disability stereotypes: Narrative identities of Brazilian female paralympians - Kirakosyan, L. (Disabilities, 2021)
The purpose of this narrative inquiry is two-fold: first, to illuminate the views and experiences of Brazilian female Paralympians that helped shape their narrative identities, and second, to develop a better understanding of the reasons behind the gender inequality in Paralympic sports.According to the International Paralympic Committee, 1671 female athletes competed in the Rio 2016 Paralympics, representing almost 40 percent of the participating Paralympians. In Rio, Brazil had the largest Paralympic delegation in its history, with 287 Paralympians, of which only 102 were women (about 35 percent). The reasons why there is a significant discrepancy between male and female Paralympic participation are highly complex and little researched, particularly in Latin American contexts. In examining the complexities of these women`s narrative identities and their relationship with social norms, I draw on the insights from disability feminism, identity theory, and disability sport to analyze and interpret the Paralympic sportswomen`s narrative accounts. Individual interviews with 20 Brazilian female Paralympians from nine different sports revealed the intricate relationships each has with social norms regarding gender, disability, sport, and the body.